Cretaceous palynoevents in the circum-Arctic region - Williams, Graham L.; Bujak, Jonathan P.; Bringué, Manuel; Fensome, Robert A.; Galloway, Jennifer M.; Nøhr-Hansen, Henrik; Blakey, Ronald (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
The Cretaceous Period was a time generally of high sea levels, peaking in the Cenomanian and Turonian. With sea-level rise, the extent of shelf seas expanded, providing broad opportunities for plankton such as cystproducing dinoflagellates, which reached their maximum species richness during the Cretaceous. Because of their abundance, species richness, rapid evolution and distinctive morphology, organic-walled dinoflagellate cysts (dinocysts) have become the most important palynological index fossils for the period. Dinocysts are almost exclusively marine, and marine successions are extensive through the Cretaceous and across the Arctic. Spores and pollen (miospores), which are almost exclusively of terrestrial origin, are less prominent as index fossils in the Early Cretaceous: taxa tend to be long-ranging and taxonomy poorly constrained. However, with the advent of angiosperms and the increasing diversity and distinctiveness in the Late Cretaceous, pollen become more useful biostratigraphically upsection. Extensive zonation schemes based on palynomorphs have been proposed from Arctic Canada, Greenland and northern Russia, but they tend to be disparate, with little commonality or mutual correlation. For that reason, we have chosen to identify Cretaceous palynological bioevents (palynoevents) that potentially extend around the Arctic. We have identified 187 bioevents: 99 first occurrences and 87 last occurrences and 129 involving dinocysts and 58 involving miospores. The bioevents have been calibrated insofar as possible to independent age control, such as biozonation schemes based on ammonites and bivalves. The relationships of each event to stages and key fossil zonal schemes is shown on chronostratigraphic plots using the 2020 version of TimeScale Creator®.